Distinct effects of treatment with two different interferon-alpha subtypes on HIV-1-associated T-cell activation and dysfunction in humanized mice. (1st March 2022) - Rout, Saurav S.; Di, Yunyun; Dittmer, Ulf; Sutter, Kathrin; Lavender, Kerry J.
Abstract : Supplemental Digital Content is available in the text Abstract : Objective: Interferon-alpha (IFN-α) has been associated with excessive immune activation and dysfunction during HIV-1 infection. However, evidence suggests specific IFN-α subtypes may be beneficial rather than detrimental. This study compared the effects of treatment with two different IFN-α subtypes on indicators of T-cell activation and dysfunction during HIV-1 infection. Design: Humanized mice were infected with HIV-1 for 5 weeks and then treated with two different IFN-α subtypes for an additional 3 weeks. Splenic T cells were assessed both immediately posttreatment and again 6 weeks after treatment cessation. Methods: HIV-1 infected triple-knockout bone marrow-liver-thymus mice received daily intraperitoneal injections of either IFN-α14 or the clinically approved subtype, IFN-α2. T cells were analysed directly ex vivo for indicators of activation and dysfunction or stimulated to determine their proliferative capacity and ability to produce functional mediators. Results: Unlike IFN-α2, IFN-α14 treatment reduced viremia and resulted in less activated CD4 + T cells and a lower naïve to effector CD8 + T-cell ratio. Despite exhibiting a reduced proliferative response, the frequency of CD8 + T cells from IFN-α14 treated mice that produced functional mediators and expressed markers of dysfunction was more similar to healthy controls than untreated and IFN-α2 treated mice. Frequencies of exhaustion marker expression remained higher in untreated and IFN-α2 treated mice 6 weeks posttreatment despite similar viral loads between groups at this timepoint. Conclusions: Treatment with different IFN-α subtypes had distinctive effects on T cells during HIV-1 infection. IFN-α14 was associated with fewer indicators of T-cell dysfunction whereas IFN-α2 treatment had little impact.